A high-coverage Neandertal genome from Vindija Cave in Croatia - Prüfer, Kay (Science, 2017)
To date the only Neandertal genome that has been sequenced to high quality is from an individual found in Southern Siberia. We sequenced the genome of a female Neandertal from ~50 thousand years ago from Vindija Cave, Croatia to ~30-fold genomic coverage. She carried 1.6 differences per ten thousand base pairs between the two copies of her genome, fewer than present-day humans, suggesting that Neandertal populations were of small size. Our analyses indicate that she was more closely related to the Neandertals that mixed with the ancestors of present-day humans living outside of sub-Saharan Africa than the previously sequenced Neandertal from Siberia, allowing 10-20% more Neandertal DNA to be identified in present-day humans, including variants involved in LDL cholesterol levels, schizophrenia and other diseases.